Individual differences and their measurement: A review of 100 years of research - SACKETT, Paul R. (Institutional Knowledge at Singapore Management University, 2017)
This article reviews 100 years of research on individual differences and their measurement, with a focus on research published in the Journal of Applied Psychology. We focus on 3 major individual differences domains: (a) knowledge, skill, and ability, including both the cognitive and physical domains; (b) personality, including integrity, emotional intelligence, stable motivational attributes (e.g., achievement motivation, core self-evaluations), and creativity; and (c) vocational interests. For each domain, we describe the evolution of the domain across the years and highlight major theoretical, empirical, and methodological developments, including relationships between individual differences and variables such as job performance, job satisfaction, and career development. We conclude by discussing future directions for individual differences research. Trends in the literature include a growing focus on substantive issues rather than on the measurement of individual differences, a differentiation between constructs and measurement methods, and the use of innovative ways of assessing individual differences, such as simulations, other-reports, and implicit measures.